Das descobertas privadas aos crimes públicos: evolução dos significados em trajectórias de droga-crime - Celina Manita (2000)
The author presents and discusses the outcomes of a study about determinations and meanings associated to drug use, crime and drug-crime relationship. The evolution of significations along drug-crime pathways are emphasized, especially on what concerns the cases that evolve from private, self-determinated drug use to drug addiction related to public (hetero-determinated) criminality.